Suppression of non‐small‐cell lung cancer A549 tumor growth by an mtDNA mutation‐targeting pyrrole‐imidazole polyamide‐triphenylphosphonium and a senolytic drug. Issue 4 (16th February 2022) - Tsuji, Kohei; Kida, Yuki; Koshikawa, Nobuko; Yamamoto, Seigi; Shinozaki, Yoshinao; Watanabe, Takayoshi; Lin, Jason; Nagase, Hiroki; Takenaga, Keizo
Abstract: Certain somatic mutations in mtDNA were associated with tumor progression and frequently found in a homoplasmic state. We recently reported that pyrrole‐imidazole polyamide conjugated with the mitochondria‐delivering moiety triphenylphosphonium (PIP‐TPP) targeting an mtDNA mutation efficiently induced apoptosis in cancer cells with the mutation but not normal cells. Here, we synthesized the novel PIP‐TPP, CCC‐021‐TPP, targeting ND6 14582A > G homoplasmic missense mutation that is suggested to enhance metastasis of non‐small‐cell lung cancer A549 cells. CCC‐021‐TPP did not induce apoptosis but caused cellular senescence in the cells, accompanied by a significant induction of antiapoptotic BCL‐XL. Simultaneous treatment of A549 cells with CCC‐021‐TPP and the BCL‐XL selective inhibitor A‐1155463 resulted in apoptosis induction. Importantly, the combination induced apoptosis and suppressed tumor growth in an A549 xenografted model. These results highlight the potential of anticancer therapy with PIP‐TPPs targeting mtDNA mutations to induce cell death even in apoptosis‐resistant cancer cells when combined with senolytics. Abstract : A short linear pyrrole‐imidazole polyamide‐triphenylphosphonium (PIP‐TPP) conjugate (CCC‐021‐TPP) targeting mtDNA ND6 A14582G mutation in non‐small‐cell lung cancer A549 cells induced cellular senescence and, when combined with the BCL‐XL inhibitor A‐1155463, triggered apoptosis in vitro and in vivo. These results highlight potential anticancer therapy with PIP‐TPPs targeting mtDNA mutations to induce cell death even in apoptosis‐resistant cancer cells when combined with senolytics.